Women of a promiscuous nature - Everhart, Donna (Kensington Publishing Corp., 2026)
Accused of "promiscuity" in 1940s North Carolina, a young woman unjustly incarcerated and subjected to involuntary medical treatment at The State Industrial Farm Colony for Women decides to fight back in this powerful, shockingly timely novel based on the long-buried history of the American Plan, the government program designed to regulate women's bodies and sexuality throughout the first half of the 20th century. The day Ruth Foster's life changes begins the same way as many others--with a walk through her North Carolina hometown toward the diner where she works. But on this day, Ruth is stopped by the local sheriff, who insists that she accompany him to a health clinic. Women like Ruth--young, unmarried, living alone--must undergo testing in order to preserve decency and prevent the spread of sexual disease. Though Ruth has never shared more than a chaste kiss with a man, by day's end she is one of dozens of women held at the State Industrial Farm Colony for Women. Some, like 15-year-old Stella Temple, are brought in at their family's request. For Stella, even the Colony's hardships seem like a respite from her nightmarish home life. Superintendent Dorothy Baker, convinced that she's transforming degenerate souls into upstanding members of society, oversees the women's medical treatment and "training" until they're deemed ready for parole. Sooner or later, everyone at the Colony learns to abide by Mrs. Baker's rule book or face the consequences--solitary confinement, grueling work assignments, and worse. But some refuse to be cowed. Against Mrs. Baker's dogged efforts and the punishing weight of authority, Ruth and other inmates find ways to fight back, resolved to regain their freedom at any cost ...